2016
DOI: 10.5194/esurf-4-327-2016
|View full text |Cite
|
Sign up to set email alerts
|

Bedrock incision by bedload: insights from direct numerical simulations

Abstract: Abstract. Bedload sediment transport is one of the main processes that contribute to bedrock incision in a river and is therefore one of the key control parameters in the evolution of mountainous landscapes. In recent years, many studies have addressed this issue through experimental setups, direct measurements in the field, or various analytical models. In this article, we present a new direct numerical approach: using the classical methods of discrete-element simulations applied to granular materials, we exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
(88 reference statements)
0
15
0
Order By: Relevance
“…In recent years, hydro-abrasion has been investigated through analytical and numerical approaches (e.g. Aubert et al, 2016;Johnson, 2014;Turowski, 2009;Turowski & Hodge, 2017;Turowski et al, 2007), experimental studies (e.g. Auel et al, 2017aAuel et al, , 2017bScheingross et al, 2014;Sklar & Dietrich, 2001), and direct measurements in the field (Arnold et al, 2020;Müller-Hagmann, 2017;Müller-Hagmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hydro-abrasion has been investigated through analytical and numerical approaches (e.g. Aubert et al, 2016;Johnson, 2014;Turowski, 2009;Turowski & Hodge, 2017;Turowski et al, 2007), experimental studies (e.g. Auel et al, 2017aAuel et al, , 2017bScheingross et al, 2014;Sklar & Dietrich, 2001), and direct measurements in the field (Arnold et al, 2020;Müller-Hagmann, 2017;Müller-Hagmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, Kench and McLean (1996) demonstrated that for nonspherical bioclastic carbonate sediment, the mobilization threshold can be lower than that predicted by the critical Shield's parameter. Additionally, in an environment where sediment is sparse, that is, the Kwajalein Island reef flat, isolated sediment grains or small collections of grains not interlocking with a bed of sediment would experience lower stabilizing frictional force, resulting in a lower mobilization threshold (Aubert et al, 2016) and potentially different friction coefficient values.…”
Section: Model Limitationsmentioning
confidence: 99%
“…Nevertheless, depending on the choice of P , our model can yield a wide range of cover functions that encompasses reported functions both from numerical modelling (e.g. Aubert et al, 2016;Hodge and Hoey, 2012;Johnson, 2014) and experiments (Chatanantavet and Parker, 2008;Inoue et al, 2014;Sklar and Dietrich, 2001) (see Figs. 4 and 5).…”
Section: Model Formulationmentioning
confidence: 99%
“…Zhang et al (2015) formulated a macro-roughness cover model, in which sediment cover is related to the ratio of sediment thickness to bedrock macro-roughness. Aubert et al (2016) directly simulated the dynamics of particles in a turbulent flow and obtained both linear and exponential cover functions. Johnson (2014) linked sediment transport and cover to bed roughness in a reach-scale model.…”
Section: Introductionmentioning
confidence: 99%